Physiological and Environmental Factors Influencing Hydrogen Production by Unicellular Green Alga Monoraphidium sp. KMITL-1 - Krutpan, Varanya; Supakriangkrai, Thaninthorn; Lohasupthawee, Pana; Phunpruch, Saranya (My University, 2025)
With the growing global energy demand and the urgent need to reduce carbon emissions, hydrogen (H2) has emerged as a promising clean energy carrier. Among various biological H2 production, green algae present a sustainable and eco-friendly alternative due to their ability to produce H2 via photobiological pathways. This study aimed to investigate H2 production by unicellular green alga Monoraphidium sp. KMITL-1, isolated from hydroponic water at the Plant Tissue Culture Laboratory, King Mongkut’s Institute of Technology Ladkrabang. The taxonomic identity of the strain, belonging to the genus Monoraphidium within the Selenastraceae family, was confirmed through morphological observation and molecular characterization using 23S plastid rRNA gene sequencing. Various physiological and environmental parameters influencing H2 production were evaluated, including cell age, cell density, nutrient deprivation, carbon source, pH, temperature, and light intensity. A 24-hour-old culture with an OD750 of 0.8 exhibited a significant increase in H2 production. The optimal medium was potassium-deprived Tris-acetate-phosphate (TAP-K) supplemented with glucose at a concentration of 350 mmol C-atom L-1. The ideal environmental conditions for H₂ production were pH 7.2, a temperature of 30 °C, and a light intensity of 60 μmol photons m-2 s-1. Under these optimized conditions, Monoraphidium sp. KMITL-1 achieved a maximum H2 production rate of 67.976 ± 1.096 μmol H2 mg Chl-1 h-1 and a cumulative H2 yield of 3,190.436 ± 2.219 μmol H2 mg Chl-1 after 72 h of incubation. These results highlight the potential of Monoraphidium sp. KMITL-1 for large-scale biohydrogen production and its applicability in the development of sustainable energy technologies.
Keywords: Carbon source; Green algae; Hydrogen; Hydrogenase activity; Nutrient deprivation